Psychological Risk Assessment with Hamilton Scales Among Menopausal Women in Chennai, South India - Logeswari; Minthami Sharon; Balaji; Angeline Grace G; Sujitha Pandian (Medsci Publications, 2023)
Introduction: Menopausal women must undergo routine mental health screenings to ensure their best mental health. This study was designed to evaluate the mental health of women going through menopause, and to associate sociodemographic and clinical factors with mental health impairment. Methodology: In this cross - sectional study, 200 menopausal women were included after getting informed consent. Data was collected using self-administered questionnaire, Hamilton Scales for Anxiety and Depression and analysis was done using SPS software. Results: The mean age of the postmenopausal women in the study was 49.5 years.  Nearly 28% of women had complete high school education and 11% were graduates. About 13% of the participants were engaged in semi-professional work, 13% in unskilled work and 8.5% in clerical jobs. The factors which were found to have a statistically significant association with mental health (p<0.05) were age at menopause, education, occupation and duration of menopause. Conclusion: Numerous initiatives including regular yoga sessions, creation of self-help groups, and the provision of calcium, iron and vitamins can aid in lowering postmenopausal women's psychological stress. This can enhance their ability to cope with menopause and its effects. With the use of information, education, and communication (IEC) efforts, the community must be made aware of menopause.